Response of smaller plankton to the saltwater barrage-altered hydrography of a tropical estuarine system on India's southwest coast. (1st July 2022) - Arunpandi, N.; Jyothibabu, R.; Jagadeesan, L.; Arya, P.M.; Rashid, C.P.; Sarath, S.
Abstract: This study examines how a large saltwater barrage [Thannermukkom barrage (TB)] in the Kochi backwaters (KBW), India's largest estuarine system on the west coast, affects the distribution of autotrophic small plankton communities ( Synechococcus, picoeukaryotes, and nanoplankton). The KBW has two distinct regions when the shutters of TB are closed during non-monsoon periods: a mesohaline to euhaline northern region downstream and a limnetic southern region upstream. The current seasonal salinity distribution in the KBW revealed a significant decrease compared to that before the establishment of TB. Considering this, we hypothesised that the human-induced hydrographical transformation associated with the functioning of TB has implications for the ecology of the smaller plankton components in the system, and to test this, smaller autotrophic plankton and hydrographical variables were collected from the KBW during three different seasons, including the Pre-Monsoon [(PRM) March–May], the Southwest Monsoon (SWM) from June to September, and the Northeast Monsoon (NEM) from November to February. Seasonally, 13 locations along the KBW were sampled, with locations 1–4 in the downstream, 5–9 in the midstream, and 10–13 in the upstream. The findings revealed that, regardless of season, a mesohaline condition in the KBW is the most conducive one that sustains an increased abundance of autotrophic pico-and nano-plankton communities. Two strains of Synechococcus (SYN) [phycoerythrin rich SYN I and phycocyanin rich SYN II] contribute nearly equally in the mesohaline region, whereas a predominance of SYN II (>90%) was found in oligohaline/limnohaline conditions. We show that TB reduces the geographic extent of the mesohaline zone in the KBW that is most conducive to maintaining a high abundance of smaller plankton communities, reducing the total abundance and biomass of the smaller plankton community in the system. Highlights: Distribution of smaller plankton in the Kochi backwaters has been impacted heavily by the saltwater barrage. Demarcated the smaller plankton as indicator in the different hydrographical settings. Comparison with salinity showed a major compositional shift in smaller plankton due to barrage. Propose smaller plankton as an easy and efficient tool to assess man-made hydrological changes.